2010
DOI: 10.1358/mf.2010.32.3.1423888
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of calcium dobesilate for its anti-cataract potential in experimental animal models

Abstract: The present study evaluated the protective action of calcium dobesilate (CDO) in various experimental models of cataract. CDO was studied in hydrocortisone-induced cataract in developing chick embryos and selenite-induced cataract in pups. CDO anti-cataract activity was also evaluated after oral and topical application as eye drops in galactose (30%) fed rats. This study was further extended to evaluate the intraocular penetration of a single dose of 1% CDO (50 microL) in rabbits. CDO exhibited significant pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The procedure previously standardized in our laboratory [6] was used for this experiment. Briefly, ten days old White leghorn chick eggs were procured from Kegg Farm (Gurgaon, Haryana, India).…”
Section: Methodsmentioning
confidence: 99%
“…The procedure previously standardized in our laboratory [6] was used for this experiment. Briefly, ten days old White leghorn chick eggs were procured from Kegg Farm (Gurgaon, Haryana, India).…”
Section: Methodsmentioning
confidence: 99%
“…Calcium is closely related to vitamin D, and studies on experimental animal models have reported that calcium could show anti-cataract activity in steroid-mediated cataracts with its antioxidant effect [27]. Paradoxically, it has also been stated that calcium could start cataract development by inducing cortical opacities following protease induction in lens epithelial cells [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…The present study was aimed to examine the preventive effects of different doses of betaine on cataract formation using in vivo chick embryo SIC model. Chick embryo SIC model has been used as an efficient animal cataract model to study the anti-cataract potential of several agents1617181920.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, chick embryo SIC model was used which was first reported by Lee et al 15. Several studies have shown that the anatomy and histology of the chick embryo lens tissues are similar in size and appearance to human lens tissues151617.…”
Section: Methodsmentioning
confidence: 99%